2016
DOI: 10.1037/com0000028
|View full text |Cite
|
Sign up to set email alerts
|

Mimic me while playing! Social tolerance and rapid facial mimicry in macaques (Macaca tonkeana and Macaca fuscata).

Abstract: Social play and tolerance are positively correlated and playful signals are more freely expressed in egalitarian than in despotic species. Macaque species are organized along a continuum from intolerant to tolerant social systems and, for this reason, they are good models to test some hypotheses about the possible linkage between communication and tolerance. We compared facial playful communication in 2 macaque species at opposite ends of the continuum: despotic Japanese macaques, Macaca fuscata, and tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 73 publications
5
90
0
Order By: Relevance
“…Previous reports have concluded that Macaca tonkeana are sensitive to variations in the affective states of other group members (Palagi et al, ; Scopa & Palagi, ). In this species, opponents show a high rate of reconciliation (Demaria & Thierry, ) and third parties are reactive to conflicts that occur in the group, thus increasing the reciprocal affiliative interactions (De Marco et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Previous reports have concluded that Macaca tonkeana are sensitive to variations in the affective states of other group members (Palagi et al, ; Scopa & Palagi, ). In this species, opponents show a high rate of reconciliation (Demaria & Thierry, ) and third parties are reactive to conflicts that occur in the group, thus increasing the reciprocal affiliative interactions (De Marco et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Agonistic and dominance behavior covaries with such traits as degree of maternal permissiveness, amount of alloparental care, form of social play, degree of kin preference among females, diversity of communicative signals, and personality dimensions (Adams et al, 2015;Ciani, Dall'Olio, Stanyon, & Palagi, 2012;Dobson, 2012;Petit, Bertrand, & Thierry, 2008;Scopa & Palagi, 2016;Thierry et al, 2008). There are also hints that in competitive situations, individuals from the more tolerant species can stay closer to each other more easily than their more intolerant counterparts, thus enabling more group members to access the same resources (Bélisle et al, 2012;de Waal & Luttrell, 1989;Matsumura, 2001;Petit, Desportes, & Thierry, 1992).…”
mentioning
confidence: 99%
“…Table summarizes variation in the style of play–fighting across these seven species, ranging from the despotic M. mulatta and M. fuscata to the egalitarian M. tonkeana and M. nigra . The general pattern is that egalitarian species, such as Tonkean macaques ( M. tonkeana ) and crested macaques ( M. nigra ), adopt a more cooperative style of social play than the competitive play–fighting seen in despotic species such as Japanese macaques ( M. fuscata ), with egalitarian species showing more reciprocal rough‐and‐tumble play (e.g., higher frequency of wrestling) and despotic species more cautious play (e.g., face‐to‐face body orientation between partners to avoid vulnerable positions; Ciani, Dall'Olio, Stanyon, & Palagi, ; Palagi et al., ; Petit et al., ; Reinhart, ; Reinhart et al., ; Scopa & Palagi, ; Thierry, , ). For example, Tonkean macaques engage in longer bouts of play and have a relatively cooperative style of play–fighting compared with the more competitive style of play–fighting in Japanese macaques, which involves different behavioural patterns and preferred body targets (Ciani et al., ; Reinhart et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…(), 8 Reinhart et al. (), 9 Scopa and Palagi (), 10 Kipper and Todt (), and 11 Nickelson and Lockard ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation